2020
DOI: 10.3390/en13040893
|View full text |Cite
|
Sign up to set email alerts
|

Combined Radiative Cooling and Solar Thermal Collection: Experimental Proof of Concept

Abstract: Climate change is becoming more important day after day. The main actor to decarbonize the economy is the building stock, especially in the energy used for Domestic Hot Water (DHW), heating and cooling. The use of renewable energy sources to cover space conditioning and DHW demands is growing every year. While solar thermal energy can cover building heating and DHW demands, there is no technology with such potential and development for space cooling. In this paper, a new concept of combining radiative cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, during the day the user can decide to apply it to heat up water or cool it down, adapting to variable energy demands of the building. The RCE concept has already been demonstrated experimentally with a prototype [7] and a model has been validated [8], whereas the ad-RCE is still under development. We aim to develop and validate a new ad-RCE model and to design, build and test a new ad-RCE prototype in the following 2 years.…”
Section: Evolving the Concept Of Rce To Ad-rcementioning
confidence: 99%
“…Thus, during the day the user can decide to apply it to heat up water or cool it down, adapting to variable energy demands of the building. The RCE concept has already been demonstrated experimentally with a prototype [7] and a model has been validated [8], whereas the ad-RCE is still under development. We aim to develop and validate a new ad-RCE model and to design, build and test a new ad-RCE prototype in the following 2 years.…”
Section: Evolving the Concept Of Rce To Ad-rcementioning
confidence: 99%
“…Results reveal that the hybrid system can cover 54% of annual heating demand and 53% of annual cooling demand. Vall et al [127,128] proposed a black painted radiative collector and emitter, in which a glass screen was employed as the cover in the solar heating mode but was replaced by a polyethylene film in the radiative cooling mode. Experimental results suggested that average solar thermal efficiency up to 49% and radiative cooling efficiency of 32% were achieved respectively.…”
Section: Other Systemsmentioning
confidence: 99%
“…Conversely, a combination of nighttime radiative cooling and solar heating can be found in Refs. 31 , 32 , 33 , 34 , 35 …”
Section: Introductionmentioning
confidence: 99%